A Liquid‐Metal‐Enabled Versatile Organic Alkali‐Ion Battery. Issue 11 (21st January 2019) - Ding, Yu; Guo, Xuelin; Qian, Yumin; Zhang, Leyuan; Xue, Leigang; Goodenough, John B.; Yu, Guihua
Abstract: Despite the high specific capacity and low redox potential of alkali metals, their practical application as anodes is still limited by the inherent dendrite‐growth problem. The fusible sodium–potassium (Na–K) liquid metal alloy is an alternative that detours this drawback, but the fundamental understanding of charge transport in this binary electroactive alloy anode remains elusive. Here, comprehensive characterization, accompanied with density function theory (DFT) calculations, jointly expound the Na–K anode‐based battery working mechanism. With the organic cathode sodium rhodizonate dibasic (SR) that has negligible selectivity toward cations, the charge carrier is screened by electrolytes due to the selective ionic pathways in the solid electrolyte interphase (SEI). Stable cycling for this Na–K/SR battery is achieved with capacity retention per cycle to be 99.88% as a sodium‐ion battery (SIB) and 99.70% as a potassium‐ion battery (PIB) for over 100 cycles. Benefitting from the flexibility of the liquid metal and the specially designed carbon nanofiber (CNF)/SR layer‐by‐layer cathode, a flexible dendrite‐free alkali‐ion battery is achieved with an ultrahigh areal capacity of 2.1 mAh cm −2 . Computation‐guided materials selection, characterization‐supported mechanistic understanding, and self‐validating battery performance collectively promise the prospect of a high‐performance, dendrite‐free, and versatile organic‐based liquid metal battery. Abstract : A versatile organic alkali‐ion battery, functioning as either a Na‐ion battery or a K‐ion battery depending on the electrolytes employed, is fabricated using a sodium–potassium (Na–K) liquid alloy as the anode and an organic cathode. This novel battery exhibits outstanding electrochemical and mechanical properties, and can be assembled into flexible devices for wearable electronics.